Beyond patent counts: a comprehensive assessment of environmental protection tax effects on innovation quality and quantity - Zhang, Jiefei; Ge, Kexin; Wang, Li (Frontiers in Environmental Science, 2025)
Our study moves beyond conventional constraints that primarily examine patent counts, establishing a novel conceptual framework that comprehensively synthesizes dual dimensions—both the volume and caliber of environmental innovations—in the aftermath of environmental taxation implementation. In contrast to prior scholarship, this investigation extends past the mere assessment of policy-driven innovation promotion, conducting an in-depth examination of how environmental fiscal measures reconfigure innovation architecture and elevate innovation excellence. Using a comprehensive panel dataset of Chinese A-share listed companies from 2012 to 2022, we employ a difference-in-differences methodology with multiple robustness checks to establish causal relationships. Our findings reveal three key insights: First, contrary to the Porter Hypothesis, EPT implementation shows a negative correlation with green innovation activities in pollution-intensive sectors, particularly pronounced among private enterprises, smaller firms, and highly competitive markets. Second, the tax policy demonstrates asymmetric effects across patent categories, predominantly constraining invention patents while having a lesser impact on utility models. Third, while the aggregate volume of environmental patent applications decreases, we document a significant improvement in mean innovation quality, especially in utility model patents. The quality-enhancement effect strengthens over time, even as the quantity-reducing impact gradually attenuates. Through detailed mechanism analysis, we identify corporate liquidity constraints and reduced R&D expenditure as primary channels through which EPT affects innovation outcomes. These findings contribute to the theoretical discourse on environmental regulation and corporate innovation by highlighting the quality-quantity trade-off in green innovation responses to environmental taxation. Our results provide important policy implications for optimizing environmental fiscal instruments to promote sustainable technological advancement while maintaining innovation quality.